2019
DOI: 10.3892/ol.2019.9954
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-497-5p inhibits proliferation and invasion of non-small cell lung cancer by regulating FGF2

Abstract: Increasing number of microRNAs (miRNAs) have been reported to play an important role in the development and progression of non-small cell lung cancer (NSCLC). In particular, microRNA-497-5p (miR-497-5p) has been proposed as a tumor suppressor miRNA in human cancers. However, the role of miR-497-5p and its potential molecular mechanism associated with NSCLC are less studied. Therefore, the role of miR-497-5p in the pathogenesis of NSCLC was investigated. In the present study, the expression of miR-497-5p was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 32 publications
(31 reference statements)
1
30
0
Order By: Relevance
“…In addition, miR‐23a‐3p overexpression inhibited mucosal melanoma cell malignancy and tumorigenicity . Furthermore, miR‐497‐5p was found reduced expression and its overexpression was found to suppress NSCLC cell growth via targeting FGF2 . EPHB6, belong to the Eph receptors family, that was found elevated expression in colorectal cancer and its overexpression accelerates colorectal cancer metastasis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, miR‐23a‐3p overexpression inhibited mucosal melanoma cell malignancy and tumorigenicity . Furthermore, miR‐497‐5p was found reduced expression and its overexpression was found to suppress NSCLC cell growth via targeting FGF2 . EPHB6, belong to the Eph receptors family, that was found elevated expression in colorectal cancer and its overexpression accelerates colorectal cancer metastasis .…”
Section: Discussionmentioning
confidence: 99%
“…18 Furthermore, miR-497-5p was found reduced expression and its overexpression was found to suppress NSCLC cell growth via targeting FGF2. 19 EPHB6, belong to the Eph receptors family, that was found elevated expression in colorectal cancer and its overexpression accelerates colorectal cancer metastasis. 20 Furthermore, reduced EPHB6 expression was found in gastric carcinoma and associated with malignancy indicators for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that the incidence of MODS in patients with paraquat poisoning was ~84% (6). miRNAs are regulatory factors that play crucial roles in regulating growth, maintaining homeostasis of organisms and mediating various pathophysiological processes of diseases, and have become important research topics (35)(36)(37). The present bioinformatics results suggested that miR-27a may be a potential regulator for IL-10, thus indicating the potential role of miR-27a in paraquat poisoning.…”
Section: Discussionmentioning
confidence: 61%
“…CK‐8 (Dojindo, Kumamoto, Japan) solution was purchased to evaluate cell proliferation according to product instructions. The experimental procedure was performed based on a previous study …”
Section: Methodsmentioning
confidence: 99%